Contradictions and conflict: A meta-ethnographic study of migrant women's experiences of breastfeeding in a new country - Schmied Virginia; Olley Hannah; Burns Elaine; Duff Margie; Dennis Cindy-Lee; Dahlen Hannah G (BMC, 2012)
Abstract Background Studies report mixed findings about rates of both exclusive and partial breastfeeding amongst women who are migrants or refugees in high income countries. It is important to understand the beliefs and experiences that impact on migrant and refugee women's infant feeding decisions in order to appropriately support women to breastfeed in a new country. The aim of this paper is to report the findings of a meta-ethnographic study that explored migrant and refugee women's experiences and practices related to breastfeeding in a new country. Methods CINAHL, MEDLINE, PubMed, SCOPUS and the Cochrane Library with Full Text databases were searched for the period January 2000 to May 2012. Out of 2355 papers retrieved 11 met the inclusion criteria. A meta-ethnographic synthesis was undertaken using the analytic strategies and theme synthesis techniques of reciprocal translation and refutational investigation. Quality appraisal was undertaken using the Critical Appraisal Skills Programme (CASP) tool. Results Eight qualitative studies and three studies reporting both qualitative and quantitative data were included and one overarching theme emerged: 'Breastfeeding in a new country: facing contradictions and conflict'. This theme comprised four sub-themes 'Mother's milk is best'; 'Contradictions and conflict in breastfeeding practices'; 'Producing breast milk requires energy and good health'; and 'The dominant role of female relatives'. Migrant women who valued, but did not have access to, traditional postpartum practices, were more likely to cease breastfeeding. Women reported a clash between their individual beliefs and practices and the dominant practices in the new country, and also a tension with family members either in the country of origin or in the new country. Conclusion Migrant women experience tensions in their breastfeeding experience and require support from professionals who can sensitively address their individual needs. Strategies to engage grandmothers in educational opportunities may offer a novel approach to breastfeeding support.